Parental Assistance with Child Emotion Regulation among Mothers of Children with Neurodevelopmental Disorder in Middle Childhood - Ardelia Clarissa Alzena; Mafaza Mafaza; Siska Oktari (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2026)
Mothers of children with neurodevelopmental disorders in middle childhood are confronted with complex parenting challenges due to limitations in their children’s socio- emotional abilities, particularly emotional dysregulation. This study aims to describe parental assistance with child emotion regulation among mothers of children with neurodevelopmental disorders in middle childhood. This study employed a quantitative method with a descriptive design involving 107 mothers of children with neurodevelopmental disorders in middle childhood in East Jakarta. Based on descriptive statistical analysis, the findings showed that 64.5% of mothers were categorized as predominantly using adaptive strategies, while 35.5% were categorized as predominantly using maladaptive strategies. However, when strategies were analyzed individually, distraction, which is classified as a maladaptive strategy, had the highest mean score, whereas expressive suppression, also categorized as maladaptive, had the lowest mean score. The implications of this study highlight the importance of psychoeducation for parents to strengthen adaptive parenting strategies in supporting the emotion regulation of children with neurodevelopmental disorders.